영산홍을 이용한 저관리 옥상녹화 시스템의 식물생육 및 토양특성 평가 - 김인혜(In-Hea Kim); 허근영(Keun-Young Huh); 신현철(Hyeon-Cheol Shin); 박남창(Nam-Chang Park) (Weon'ye gwahag gi'sulji, 2010)
Recent urban concerns over environmental problems have furthered interest in green roof system. Plant growth and load bearing capacity of an underlying roof are key factors to determine an optimal system. This study was carried out to develop an optimal extensive green roof system for shrubs assessing the effects of substrate type and soil depth on the growth of $Rhododendron$ $indicum$ Sweet. in the experimental systems with different soil types and depths from 2001 to 2008. Substrate types of perlite alone and blended with sandy loam (v/v, 1:1) were used on the experimental systems with depths of 30 cm, 45 cm, and 60 cm. The survival rate of the plants on the perlite alone + 45 cm soil depth system (RS-A-45) was 100% during the experimental period, while those on the perlite alone + 30 cm soil depth system (RS-A-30) and perlite blended + 60 cm soil depth system (RS-B-60) showed 33% and 67%, respectively, in 2008. The overall plant growth and soil properties of RS-A-45 were superior to the others. At 8 years after installation, the total weight of RS-A-45 including plant fresh weight was about $376.6kg{·}m^{-2}$ in field capacity indicating RS-A-45 can be optimal extensive and light weight green roof system. 최근 도시의 환경문제로 인하여 옥상녹화에 많은 관심이 집중되고 있다. 옥상녹화 기술의 핵심은 식물의 생육을 건전하게 유지하는 동시에 건축물에 미치는 하중을 최소화할 수 있는 토양층을 조성하는 것이다. 본 연구는 옥상 환경에서 관목류의 생육을 건전하게 유지하면서 하중을 최소화할 수 있는 최적의 저관리 녹화 시스템을 구명하기 위한 연구의 일환으로서 상록관목인 영산홍을 식물재료로 선정하고 펄라이트를 주재료로 한 토심 30cm, 45cm, 60cm의 인공토양층을 건축물 옥상에 조성한 후, 2001년부터 2008년까지 식물 생육, 토양의 물리적 화학적 특성 변화, 건축물에 미치는 하중에 대한 평가를 수행하였다. RS-A-45와 RS-A-60에서는 실험 기간 동안 100%의 식물 생존율을 나타냈고 RS-A-30과 RS-B-60에서는 2008년에 각각 33%와 67%의 식물 생존율을 나타냈다. RS-A-45에서는 지속적으로 가장 높은 생육량이 나타났고 토양의 물리적 화학적 특성도 가장 우수하게 나타났다. 조성 후 8년이 경과한 시점에서 식물체를 포함한 포장용수 시 RS-A-45의 총중량은 $376.6kg{·}m^{-2}$으로 옥상 녹화 허용 적재하중인 $500kg{·}m^{-2}$보다 상당히 낮아 하중 측면에서도 적합한 것으로 평가되었다.